О‘SMIR FUTBOLCHILARNING FAOLIYATIDAGI TO‘SIQ VA QIYIN VAZIYATLARGA PSIXIK BARQARORLIKNI TA’MINLASH ASOSI - Xaitov, A.U. (SCIENCE and SOCIETY, 2024)
This article identifies the types of obstacles and difficult situations that arise in the activities of teenage football players and the level of their influence. The volitional qualities necessary to increase the athletes’ resistance to such situations have been identified. In order to maintain the mental stability of teenage football players during competitions, a relation between obstacles and difficult situations with the components of mental stability has been identified.